Impact of Social Media upon Juvenile Delinquency in Basra Central Prison and AL- Maqal Police Station (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: This study aimed to determine the impact of social media domains. And find out the know whichamong social media sites were mostly used by the juveniles.Methodology: Quantitative design (a descriptive study) of one hundred juveniles were selected. All thejuveniles for both sexes as delinquent who were temporarily detained in police station convicted of felony,crime or misdemeanor who is awaiting trial; and delinquent convicted of crime or felonies for rehabilitationor punishment convicted of misdemeanors and major offenses in central prison; juveniles who were at 14-17years, for the period from 3rd February 2019 until 4th April 2019 in AL-Maqal Police Station and 14th April2019 until 14th May 2019 in Basra Central Prison. The collection of data is performed out of the utilizationof developed questionnaire and by means of structured interview technique with the subjects who wereindividually interviewed by the using of Arabic version of the questionnaire in Basra Central Prison andAL- Maqal Police Station.Results: The results of the study indicate more than half 59% of age 16-17 year; more than three-quarters82% were male; also more than three-quarters 77% living in urban and in slum area 51%. The resultsrevealed that the samples of social media were (100%) watch movies; (96.5%) used chat; (86%) play game;while (100%) use the you tube; (97.7%) use face book; while (98.8%) browse the violence program. Themore types of offenses and misdemeanor committed by the Juveniles were (18%) theft; and (16%) drugabuse.
Keywords: Impact; Social Media; Juvenile Delinquency; Prison; Police Station.